Microfluidic platforms for modeling biological barriers in the circulatory system. Issue 4 (April 2018) - Yu, Fang; Selva Kumar, Nivasini D/O; Choudhury, Deepak; Foo, Lynette C.; Ng, Sum Huan
Graphical abstract: Highlights: Biological barriers regulate homeostasis and create challenges for drug delivery. Microfluidic platforms can be used to recapitulate biological barriers in-vitro. Microfluidic biological barrier platforms are ideal for mechanistic studies. Pathological conditions can be created with microfluidic platforms for drug testing. Abstract : Microfluidic platforms have recently become popular as in vitro models because of their superiority in recapitulating microenvironments compared with conventional in vitro models. By providing various biochemical and biomechanical cues, healthy and diseased models at the organ level can be applied to disease progression and treatment studies. Microfluidic technologies are especially suitable for modeling biological barriers because the flow in the microchannels mimics the blood flow and body fluids at the interfaces of crucial organs, such as lung, intestine, liver, kidney, brain, and skin. These barriers have similar structures and can be studied with similar approaches for the testing of pharmaceutical compounds. Here, we review recent developments in microfluidic platforms for modeling biological barriers in the circulatory system. Teaser: Microfluidic platforms offer a powerful approach to recapitulate complex cellular-level physiology and tissue-tissue interactions at biological barriers for the purpose of drug testing and tissue engineering.